Semen characteristics of the swamp buffalo (bubalus bubalis) - Jainudeen, Mohamed Razeen; Bongso, T. A.; Dass, S. (Elsevier, 1982)
The semen characteristics were studied in 182 ejaculates collected with a bovine artificial vagina from five swamp buffalo (Bubalus bubalis) bulls. The mean values were: volume, 2.9 ml; general motility, 70.7%;live (unstained) sperm, 86.5%;abnormal sperm, 10.3%;intact acrosomes, 82.4%;sperm concentration, 1.06 X10· cells/ml and total sperm/ ejaculate, 3.18 X 109 cells/m!. Among the sperm abnormalities noted were "knobbed" acrosome, abaxial implantation, the "Dag" defect and the corkscrew midpiece. There were no significant (P > 0.05) monthly variations for any of the semen characteristics studied.